Tingkat Kepuasan Konsumen Buah Lokal dan Buah Impor Terhadap Pelayanan di Pasar Swalayan â€œJumboâ€ di Kota Manado - Riheld H. Lomboan; Grace A.J. Rumagit; Mex F. L. Sondakh; Gene H.M. Kapantow (COCOS, 2015)
ABSTRACTRiheld Hiskia Lomboan. Consumer Satisfaction For Local Fruits and Fruit Import To The Services in "Jumbo" Supermarket in Manado Municipality (under the guidance of Grace A. J. Rumagit as chairman, Mex. F. L. Sondakh and Gene H. M. Kapantow as members).Customer satisfaction is very important factor for entrepreneurs in running a business. Consumer satisfaction in the can can lead to repeat purchases even consumers may be loyal to the product. The objective of this research is to determine the level of customer satisfaction to the service at Jumbo Supermarkets in Manado municipality through the aspects of reliability, responsiveness, Assurance, Empathy, and Tangibles.This research uses primary data and secondary data. Sampling method in this research is Accidental Sampling.The research result showed that the level costumer satisfaction for local fruit and imported fruit based on reliability, responsiveness, assurance, empathy and tangibles was categorized as satisfy and more satisfy to the services at Jumbo Supermarket.Keywords: Consumer Satisfaction, FiveAspects of Consumer Satisfaction